Conversion of pencil graphite to graphene/polypyrrole nanofiber composite electrodes and its doping effect on the supercapacitive properties. Issue 9 (29th December 2014) - Sudhakar, Y.N.; Vindyashree; Smitha, Vidya; Prashanthi; Poornesh, P.; Ashok, R.; Selvakumar, M.
<x xml:space="preserve">Abstract</x> Graphene platelets were synthesized from pencil flake graphite and commercial graphite by chemical method. The chemical method involved modified Hummer's method to synthesize graphene oxide (GO) and the use of hydrazine monohydrate to reduce GO to reduced graphene oxide (rGO). rGO were further reduced using rapid microwave treatment in presence of little amount of hydrazine monohydrate to graphene platelets. Chemically modified graphene/polypyrrole (PPy) nanofiber composites were prepared by in situ anodic electropolymerization of pyrrole monomer in the presence of graphene on stainless steel substrate. The morphology, composition, and electronic structure of the composites together with PPy fibers, graphene oxide (GO), rGO, and graphene were characterized using X‐ray diffraction (XRD), laser‐Raman, and scanning electron microscopic (SEM) methods. From SEM, it was observed that chemically modified graphene formed as a uniform nanocomposite with the PPy fibers absorbed on the graphene surface and/or filled between the graphene sheets. Such uniform structure together with the observed high conductivities afforded high specific capacitance and good cycling stability during the charge–discharge process when used as supercapacitor electrodes. A specific capacitance of supercapacitor was as high as 304 F g−1 at a current density of 2 mA cm−1 was achieved over a PPy‐doped graphene composite. POLYM. ENG. SCI., 55:2118–2126, 2015. © 2014 Society of Plastics Engineers